Decrease in eccentric quadriceps and hamstring strength in recreational alpine skiers after prolonged skiing. Issue 1 (10th August 2015) - Koller, Arnold; Fuchs, Birgit; Leichtfried, Veronika; Schobersberger, Wolfgang
Abstract : Background: To effectively prevent injury in recreational alpine skiing, it is important to identify modifiable risk factors that can be targeted through exercise and training. Fatigue is a potential risk factor in recreational skiing, but no investigations have evaluated concentric/eccentric quadriceps and hamstring fatigue in recreational skiers. We tested the hypothesis that recreational skiing is associated with more pronounced eccentric as compared with concentric muscle fatigue. Methods: Twenty-four healthy and fit recreational skiers (14 male and 10 female) performed an isokinetic muscle test 1 day before, 1 h after, and 24 h after a 4 h skiing session. The testing protocol consisted of concentric and eccentric quadriceps and hamstring contractions for both legs. Results: Eccentric peak hamstring torque (both thighs) and eccentric peak quadriceps torque (left thigh) were reduced in male and female participants (p<0.05). Reduced peak torques were still present 24 h after the skiing session. There were no other significant findings. Summary: Recreational skiing is associated with prolonged (at least 24 h) eccentric quadriceps (left thigh) and hamstring (both thighs) fatigue in men and women. Eccentric quadriceps and hamstring fatigue may be a potential injury risk factor in male and female recreational skiers. This provides some justification for judicious use of additional eccentric training modalities for alpine skiing.